Sunshine and rainbows : the development of gay and lesbian culture in Queensland - Moore, Clive, 1951- (St Lucia, Qld. : University of Queensland Press, 2001)
A history of the development of homosexuality as an Australian subculture. Proceeding chronologically from the 1820s through to the vibrant alternative culture that exists in 2000, this book argues that the manner in which gay and lesbian identity has been constructed in Queensland is typical of Australia generally.
Machine derived contents note: Chapter One: Symbols and Meanings 1 -- From Gay to Queer and Beyond 3 -- Inventing the Moder Homosexual 8 -- From Stigma to Pride: The Medical Profession and Homosexuality 12 -- Lesbians, Romantic Friends and Boston Marriages 15 -- Mardi Gras and Carnivale 18 -- Wearing a Pink Triangle 20 -- The Rainbow Flag 22 -- Chapter Two: Colonial Law and Individuals 25 -- Homosexuality in Colonial Queensland: The Evidence 27 -- Enough Evidence to Convict: Townsville, 1871 33 -- That Abominable Crime: Homosexuals and the Law in -- Colonial Queensland 40 -- Was Queensland's First Premier Gay? Robert Herbert and -- John Bramston, 1860s 43 -- Luigi Maria D'Albertis: The Bird of Paradise Man, 1870s 45 -- 'A Gay Young Bachelor Fond of Fancy Dancing': -- George Seymour, Earl of Yarmouth, 1890s 46 -- Chapter Three: Race and Sexuality: -- Relationships with the Other 51 -- Aboriginal Men in Colonial Queensland 51 -- 'Me Got Like Long You': Melanesians in Colonial Queensland 53 -- 'Hello Mister, Where You Go?': Asians in Colonial Queensland 55 -- The Papuan and the Blond Chauffeur, Brisbane 1926 57 -- Chapter Four: Masculinity and the Beginnings of -- a Subculture 60 -- Colonial Demographics 61 -- Camping by a Billabong?: Swaggies and Sex 64 -- 'He Tried to Make My Nature Flow': Boys and Sex in -- Colonial Queensland 65 -- Brisbane's Boarding Houses: Men in Shared Accommodation 67 -- Cruising for Sex 69 -- Chapter Five: 'Passing Women', Spinsters and -- Bachelors, 1900s 74 -- Brisbane's 'Passing Woman': 'William' Marion Edwards, 1906 75 -- 'Monte' Punshon, 1882-1989: An Extraordinary Woman 79 -- Professional Spinsters: Lilian Cooper and Josephine Bedford 81 -- Professional Bachelors: Isaac and James Mayne 83 -- Mollies, Fairies and Queens: Brisbane, 1907 85 -- The Coffee-Room Class and the Spring Hill Push, 1907 86 -- Chapter Six: Cissies, Cinemas and a Bad -- Baronet, 1910s-1930s 90 -- Behind the Buggy Shed in Brandon, 1911 90 -- Brisbane's 'Cissies' in 1920 92 -- Going to the Movies: Mackay, 1922 95 -- The Great Depression, 1930s 96 -- Baronet of Boggo Road: Sir Siddartha Affleck, 1937-41 98 -- Beats and Possession of Public Space 101 -- Chapter Seven: 'Tropical Sexy Animality': -- Queensland at War, 1942-1945 105 -- 'Over-Sexed, Over-Paid and Over-Here': -- Americans in Queensland 108 -- Comrades-in-Arms: Australia's Fighting Men 111 -- Naked Youths Wanted: Brisbane, 1940 115 -- Down by the Creek: Atherton, 1943 116 -- Snowdropping: Brisbane, 1945 117 -- Chapter Eight: Bohemia, Bars and Balls, 1940s-1960s 120 -- The Pink Elephant Cafe, 1946-49 123 -- Police Entrapment: Brisbane, 1950s 126 -- Movie Houses, Hotels and Coffee Shops 129 -- 'Perverts', 'Inverts' and the Medical Profession 131 -- Toye De Wilde's Brisbane, 1950s-1960s 133 -- Brisbane's Queen's Birthday Ball 135 -- Queensland University: Semper Floreat, 1969 138 -- Chapter Nine: Coming of Age: The Contemporary -- Gay Scene, 1970s-1990s 142 -- Coming Out in the 1970s 142 -- Queensland's Gay Venues, 1960s-1980s 143 -- Poofs in the Park: Townsville, 1980 147 -- Queensland's Beats, 1980s-1990s 149 -- Personal Advertisements 155 -- Chapter Ten: Gay Liberation, Law Reform and -- HIV/AIDS, 1970s-1980s 161 -- The Stonewall Riot and Gay Liberation 161 -- Campaign Against Moral Persecution Incorporated: CAMP Inc, 1970-85 163 -- Recognition in Townsville, 1976-90 167 -- The Greg Weir Campaign, 1977-83 171 -- Queensland AIDS Council Beginnings, 1985-87 175 -- Queensland Association for Gay Law Reform, 1988-91 183 -- Chapter Eleven: Gay/Lesbian/Queer Culture in the 1990s 190 -- From Subculture to Mainstream Culture 190 -- Law Reform 193 -- Gay and Lesbian Culture and the Media 195 -- Gay Men and HIV/AIDS 196 -- Brisbane Events and Venues 199 -- Drag Entertainers, Transgenderism and Transsexualism 203 -- The Regions 208.
Includes index.
Bibliography: p. [219]-228.
Keywords: Lesbians -- Queensland -- History; Gay men -- Queensland -- Social life and customs; Gay men -- Queensland -- History; Lesbians -- Queensland -- Social life and customs; Homosexuality; Queensland; History; Social behaviour; Subcultures